Treatment of palm oil mill effluent using sandwich ultrafiltration technique - Azmi, Nazatul Shima (2015)
Nowadays, the treatment of palm oil mill effluent (POME) has become a major critical issue in Malaysia that needs to be highlighted. This is due to the extreme organic matter in POME that needs to be treated properly to tackle the environmental issue. POME is a thick brownish viscous liquid waste with an unpleasant odour, and high in colloidal suspension and organic matter. With the needs to solve the problems in terms of environmental protection, economical viability, and sustainable development, a recent innovative ultrafiltration technique using multiple membranes known as “sandwiches membrane”, has been extended for POME treatment. This work was carried out to evaluate the potential of pre-treatment methods (adsorption-settling-surface filtration) prior to ultrafiltration treatment and to investigate the potential of ultrafiltration membrane using single and sandwich configurations to reclaim clear water in the POME. This work is divided into two parts which are: (1) pre-treatment stage prior to ultrafultration membrane and (2) POME treatment using sandwich membranes. For the pre-treatment of POME prior to ultrafiltration there were two stages involved; adsorption with settling treatment and surface filtration. In the first stage, the combined effects for adsorption with settling experimental conditions such as adsorbent dosage, treatment time and stirring speed in one hour settling time were investigated. The performance of the adsorption and settling stage using palm kernel shell-based activated carbon (PKS-AC) was based on the analysis of the suspended solid. The supernatant was then pipette out and subjected to simple surface filtration, under vacuum through Whatman® qualitative filter paper, Grade 4 (20-25 μm) and finally to Whatman® qualitative filter paper, Grade 3 (6 μm) before proceeding to the ultrafiltration process. For ultrafiltration membrane treatment, dead-end filtration mode was used. Two 5 kDa flat sheets regenerated cellulose (RC) ultrafiltration membranes were sandwiched together in various orientations without any spacer in between. The effect of operating pressure, stirring speed and pH on the permeate flux and qualities namely total solid, dissolved solid, suspended solid,biological oxygen demand (BOD5), chemical oxygen demand (COD),and turbidity were also investigated. The pollutant concentration percentage reduction for the first stage of pre-treatment using 0.20g/L of PKS-AC at 39.82 rpm stirring speed in 35.94 min and 60 min of sedimentation time of POME showed a significant reduction in term of total solid (67.30%), dissolved solid (47.11%), suspended solid (71.26%), BOD5 (63.23%), COD (42.38%) and turbidity (63.31%) respectively. In the second stage of pre-treatment, the pollutant concentration was further reduced to 65.36%, 48.75%, 87.57%, 84.5%,48.9% and 78.9% for total solid, dissolved solid, suspended solid, BOD5,COD and turbidity respectively. After the pre-treatment stage, the membrane technique was applied with purpose to further reduce the pollutant concentration and reclaiming the crystal clear water that complied with WHO water reuse standard. Result for single membrane was compared to those of sandwich with various configurations. Interestingly, SB-sandwich configuration with bottom membrane in the reverse orientation significantly reduced almost 99% of pollutant in raw POME. The best conditions using SB-sandwich was achieved at pH 8,600 rpm of stirring speed and by applying 2 bar of operating pressure for 90 min of operating time with 47.24 L/m2h of permeate flux. Applying these conditions successfully reclaimed clear water with low concentration of total solid (138 mg/L), dissolved solid (123 mg/L),suspended solid (15 mg/L), BOD5 (90 mg/L), COD (113.3 mg/L) and turbidity (0.8 NTU) from POME. Moreover, by comparing between the single and SB-sandwich membrane, showed some differences in pollutant reduction: total solid (11.45%), dissolve solid (0.28%),suspended solid (53.85%), BOD5 (60%), COD (14.12%) and turbidity (70.12%). Hence, by applying the combination technique of adsorptionsettling- surface filtration (pre-treatment) with sandwich membrane ultrafiltration technique successfully treat POME and reclaim crystal clear water that complied with WHO water reuse standard.